ANALYSE THE EFFECTIVENESS OF MACROPRUDENTIAL INDICATORS IN REDUCING CREDIT RISK IN THE BANKING SECTOR - Deni wahyudi; Wahyu Fitrah; Taufiq Chaidir (Journal of Finance, Economics and Business, 2024)
In the face of changing economic conditions, macroprudential policies have emerged as a very important tool to manage credit risk in the banking industry. The objective of this study is to evaluate how well various macroprudential policy tools, including countercyclical capital buffer (CCB), loan-to-value ratio (LTV), and debt-to-income ratio (DTI), mitigate credit risk. According to a research study, CCB helps banks become more resilient in the face of challenging economic times, while LTV and DTI rules have proven effective in reducing dangerous credit expansion in the housing sector. However, there are several obstacles in the implementation of these policies, including delays and regulatory evasion. This paper recommends the strengthening of more adaptive policy instruments, improved coordination between macroprudential and monetary policies, and the need for periodic evaluation of existing policies. We hope that by implementing these recommendations, financial stability can be maintained, and credit risk in the banking sector can be effectively minimized. Keywords: financial stability, credit risk, loan-to-value, debt-to-income, macroprudential regulation, and countercyclical capital buffers.